Acute Toxicity, Biodistribution, and Pharmacokinetics Studies of Pegylated Platinum Nanoparticles in Mouse Model. Issue 7 (13th May 2021) - Mukherjee, Sudip; Bollu, Vishnu Sravan; Roy, Arpita; Nethi, Susheel Kumar; Madhusudana, Kuncha; Kumar, Jerald Mahesh; Sistla, Ramakrishna; Patra, Chitta Ranjan
Abstract : Pegylated colloidal platinum nanoparticles (PEG‐PtNPs) are widely used as a potential agent for diagnosis and therapy of various diseases including cancer. Prior to any preclinical applications, detailed investigations of toxicity, biodistribution, clearance, and pharmacokinetics (PKs) of new nanomaterials are essential. Extensive toxicological studies of PEG‐PtNPs are not reported in a systematic manner elsewhere. Herein, acute toxicity of PEG‐PtNPs is thoroughly investigated in mouse model. Prior to study in mice, a hemolytic analysis is performed with PtNPs that displays biocompatible nature. Administration of a single intraperitoneal dose of PEG‐PtNPs (10 and 50 mg kg −1 body weight) in mice does not induce any gross pathological changes. The data obtained from hematology, serum biochemistry, and histopathological analysis indicate no significant changes except for moderate nephrotoxicity at the higher dose. In addition, a PK analysis displays a maximum retention time and elimination half‐life at 10 mg kg −1 b.w. dose. Biodistribution studies demonstrate maximum accumulation of platinum in spleen tissue and tail of mice. Finally, detection of platinum in feces and urine confirms their excretion through a hepatobiliary system. Altogether, this study indicates that 10 mg kg −1 b.w. therapeutic dose of PEG‐PtNPs is safe for their potential future application in cancer theranostics. Abstract : Acute toxicity of pegylated platinum nanoparticles (PEG‐PtNPs) is investigated in a mouse model with 10 and 50 mg kg −1 b.w. doses with no gross pathological changes. No toxicity is observed at low dose. Bioaccumulation in spleen and tail and sustained excretion is witnessed. This study indicates that 10 mg kg −1 b.w. dose of PtNPs is safe for clinical applications.